P-080 IBD Health Maintenance Is More Than Skin Deep: Counseling Skin Protective Practices May Be Inadequate for Immune-Suppressed Patients. (March 2016) - Waseem, Najeff; Baig, Kamal; Caldis, Matthew; Chablaney, Shreya; Nassereddine, Samah; Zhang, Jennie; Dougherty, Timothy; Borum, Marie
Abstract : Background: Patients with inflammatory bowel disease (IBD) are at increased risk for cutaneous malignancies. This elevated risk is further augmented by the use of immunosuppressive therapy. While these medications have been instrumental in the treatment of IBD, the potential adverse effects associated with their use require proper patient education and counseling. It is recommended that individuals with IBD who are treated with immunosuppressants be counseled regarding preventive measures to reduce their risk of skin cancer. This study aims to examine differences in physician counseling practices regarding skin cancer risk and prevention for IBD patients on immunosuppressive therapy. Methods: A retrospective review was conducted using an electronic medical record of consecutive IBD patients seen during a 12-month period for IBD surveillance colonoscopy at an urban academic medical center. Data regarding patient race or ethnicity, IBD type and extent, current treatment regimen, documentation of counseling regarding skin cancer and preventive practices, and colonoscopic findings were compiled into a database created with Microsoft Excel. Patient confidentiality was maintained. Statistical analysis was performed using Fisher's exact test, with statistical significance set at P < 0.05. The study was approved by the university institutional review board. Results: The medical records of 136 IBD patients were reviewed. There were 57 (41.9%) men and 79 (58.1%) women, with a mean age of 47.3 years. Thirty-eight (27.9%) were on immunomodulator therapy, with 28 on monotherapy and 10 on immunomodulator and a biologic. Seventeen (12.5%) patients were on biologics alone. There were 81 patients were managed with neither an immunomodulator nor a biologic medication. Nine of 28 patients (32%) on immunomodulator monotherapy, 8 of 10 patients (80%) on immunomodulator and biologic combination therapy, and 7 of 17 patients (41%) on biologic monotherapy received skin cancer/protective practices counseling or a dermatology referral. Twenty-two of 81 patients (27%) who were not on immunomodulators or biologics received counseling or a referral. Patients on an immunologically active medication were more likely to receive skin cancer-related health maintenance recommendations than those IBD patients who were not ( P = 0.0356). Additionally, IBD patients on immunomodulator and biologic combination therapy were more likely ( P = 0.0232) to receive skin protective practice counseling or dermatology referral. Conclusions: IBD patients are at an increased risk for skin cancers. This risk may be related to the underlying disease, medications, or both. Immune suppression has been associated with an additional increase in the risk for skin cancer. This study revealed that <50% of patients received counseling regarding skin protective activities or dermatology referral. While this study is limited due to size and single institution design, it suggests that increased efforts should be made to enhance counseling about skin cancer risk to optimize IBD patient care.